The EFFECTIVENESS OF MANGO LEAF EXTRACT SUPPLEMENTATION (MANGIFERA INDICA L.) ON METABOLIC DISEASE PANEL OF WISTAR RATS (RATTUS NORVEGICUS) INDUCED BY HIGH-FAT DIET: Diabetes, Glucosa, Mango Leaf, Supplement - Gilang, Gilang Ramadhan; Ramadhan K., Muhammad Zoel Vitra; Azzuhdi, Faiz Adlan; Azzahra, Nabila; Nurlina; Zahrani, Putri Dyah; Amriani, Rini; Sari, Dwi Kesuma; Bahmid, Nur Alif; Andini, Nurul Sulfi (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2026)
High-calorie foods can cause obesity if consumed in excess. Obesity occurs due to excessive fat accumulation in the body. Excess weight is a major risk factor for secondary disorders in pets, such as diabetes mellitus. Diabetes mellitus occurs due to high blood glucose levels. Mango leaf extract contains bioactive compounds that can lower and normalise blood glucose levels and can be used as a supplement. This study aims to determine the effectiveness of mango leaf extract supplementation induced by a high-fat diet on blood glucose levels. This study used arumanis and golek mango leaf. The methods used were extraction and in vivo testing. Extraction was performed on mango leaf, and the extraction results were administered to test animals in vivo. The phytochemical results showed that arumanis and golek mango leaf contain flavonoids, tannins, alkaloids, and saponins. The results showed that arumanis mango leaf extract was more effective in lowering blood glucose levels than golek mango leaf extract. These findings are expected to contribute to the development of knowledge about supplements and drug substitutes, as well as to identify more practical methods for drug therapy for diabetes mellitus in pets.